2020
DOI: 10.1016/j.kint.2020.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl iron and iron dextran therapies cause adverse effects on bone health in juveniles with chronic kidney disease

Abstract: The Nijmegen Biomedical Study is a population-based cross-sectional study conducted in the eastern part of the Netherlands. As part of the overall study, we provide reference values of estimated glomerular filtration rate (GFR) for this Caucasian population without expressed risk. Age-stratified, randomly selected inhabitants received a postal questionnaire on lifestyle and medical history. In a large subset of the responders, serum creatinine was measured. The GFR was then measured using the abbreviated Modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…However, iron suppressed bone formation markers, reduced trabecular parameters, and caused cortical thinning. ( 63 ) Bone properties are not currently being examined as primary endpoints in ongoing HIF‐PHI clinical trials but may be an important outcome to examine in the future as these drugs become fully available. Several in vitro studies have shown that stabilized HIF, through genetic or chemical treatment, induced FGF23 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, iron suppressed bone formation markers, reduced trabecular parameters, and caused cortical thinning. ( 63 ) Bone properties are not currently being examined as primary endpoints in ongoing HIF‐PHI clinical trials but may be an important outcome to examine in the future as these drugs become fully available. Several in vitro studies have shown that stabilized HIF, through genetic or chemical treatment, induced FGF23 expression.…”
Section: Discussionmentioning
confidence: 99%
“…We used a high-adenine diet mouse model of CKD ( 8 ) ( Figure 1A ). CKD mice developed severe kidney fibrosis ( Figure 1B ) and displayed systemic hypoferremia with low serum iron, low transferrin saturation, and high serum soluble transferrin receptor levels, ( Supplemental Figure 1 ; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.159235DS1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that chronic parenteral administration of iron dextran improves kidney function in juvenile mice with adenine-induced CKD ( 8 ). Similarly, ferric citrate coordination complex improved kidney function in 5/6-nephrectomized rats ( 9 ) and in juvenile mice with Alport syndrome ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pre-clinical CKD models, differential effects of iron therapy on kidney function and fibrosis have been observed, depending on the specific iron preparation and the route of administration 70 . For instance, in one study of mice with adenine diet-induced CKD, oral carbonyl iron worsened kidney function, but intraperitoneal iron dextran improved kidney function, a difference possibly contributed to by the systemic pro-inflammatory effect of chronic oral carbonyl iron administration 71 .…”
Section: Discussionmentioning
confidence: 99%